2018
DOI: 10.3324/haematol.2018.198812
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of venetoclax monotherapy in patients with relapsed, refractory mantle cell lymphoma after Bruton tyrosine kinase inhibitor therapy

Abstract: Efficacy of venetoclax monotherapy in patients with relapsed, refractory mantle cell lymphoma after Bruton tyrosine kinase inhibitor therapy early clinical data on the combination of ibrutinib-venetoclax (n=24) suggest safety, high complete metabolic responses (71%) and high minimal residual disease-negativity (67% marrow; 8-color flow cytometry).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(73 citation statements)
references
References 15 publications
1
71
0
1
Order By: Relevance
“…This initial report paved the way for landmark clinical trials of ibrutinib in MCL and other B‐cell NHLs . Our group has been involved in various clinical trials with ibrutinib, acalabrutinib, venetoclax (a Bcl2 inhibitor), and their combinations with anti‐CD20 monoclonal antibodies (mAb), rituximab, or with obinutuzumab. Furthermore, we are characterizing ibrutinib, acalabrutinib, and venetoclax‐refractory MCL and championing the CAR‐T cell clinical trials (Zuma‐2) in MCL in the United States.…”
Section: Advances In the Treatment Of MCLmentioning
confidence: 99%
See 1 more Smart Citation
“…This initial report paved the way for landmark clinical trials of ibrutinib in MCL and other B‐cell NHLs . Our group has been involved in various clinical trials with ibrutinib, acalabrutinib, venetoclax (a Bcl2 inhibitor), and their combinations with anti‐CD20 monoclonal antibodies (mAb), rituximab, or with obinutuzumab. Furthermore, we are characterizing ibrutinib, acalabrutinib, and venetoclax‐refractory MCL and championing the CAR‐T cell clinical trials (Zuma‐2) in MCL in the United States.…”
Section: Advances In the Treatment Of MCLmentioning
confidence: 99%
“…Results from the ibrutinib with venetoclax combination trial were described above in the ibrutinib section. Venetoclax has great potential in MCL treatment, even among patients who have progressed on BTK inhibitors (53% ORR) . Of late, a few studies have reported venetoclax‐resistant mutations in CLL, and the mechanism of venetoclax resistance is being studied in MCL.…”
Section: Advances In the Treatment Of MCLmentioning
confidence: 99%
“…In patients with ibrutinib‐resistant RRMCL, the optimal therapeutic approach remains a matter of debate. Recently, Eyre et al observed an ORR of 53% (18% CR, 35% PR) to venetoclax monotherapy in patients with RRMCL that was pretreated with ibrutinib, and among the patients who were primarily resistant to ibrutinib, the ORR to venetoclax was 38% …”
Section: Resultsmentioning
confidence: 99%
“…2 Venetoclax is a potent selective oral inhibitor of the BCL2 antiapoptotic protein, with demonstrated efficacy in relapsed or refractory (R/R) chronic lymphocytic leukemia (CLL) 3,4 and mantle cell lymphoma. 5,6 In contrast, 2 cases of R/R T-PLL treated with venetoclax monotherapy demonstrated only moderate and transient activity. 7 There are no other published in vivo data on the use of venetoclax in T-PLL.…”
Section: Introductionmentioning
confidence: 98%